Implantable microneedles with an immune-boosting function for effective intradermal influenza vaccination. (1st October 2019) - Chen, Yu-Hung; Lai, Kuan-Ying; Chiu, Yu-Hsiu; Wu, Yan-Wei; Shiau, Ai-Li; Chen, Mei-Chin
Graphical abstract: Abstract: This study details effective influenza vaccination via sustained intradermal (ID) release of vaccines using implantable and patch-free chitosan microneedles (MNs). The microneedle (MN) patch is composed of vaccine-loaded chitosan MNs with a dissolvable supporting array that gives extra length for complete insertion of MNs and is dissolved within the skin during insertion. Chitosan MNs can be quickly and entirely implanted into the dermis to function as a depot and an immune-boosting agent for the extended release of vaccines and simultaneous activation of the immune system. We found the influenza virus-specific antibody levels induced by chitosan MN vaccination were significantly higher than those elicited by intramuscular (IM) immunization with influenza vaccine alone. The MN induced immune-enhancing effect was obvious 4 week after the vaccination and lasted for at least 16 weeks. Most importantly, MN-immunized mice were completely protected from H1N1 viral challenge without major weight loss, whereas mice receiving IM injection at the same dose had a mortality rate of 60% and experienced notable weight loss after challenge. Our results suggest that the chitosan MNs cannot only be a viable tool for precise ID vaccine delivery but also exert strong adjuvanticity to enhance vaccine potency and induce protective immunity against influenza virus infections. Statement of Significance: There is an urgent need for generating a new vaccination strategy to address the threat of global pandemic influenza. This study presents implantable chitosan microneedles (MNs) with immune-boosting function for effective influenza vaccination. We demonstrate that the chitosan MN can not only be an efficient tool for sustained intradermal delivery but also serve as an immunological adjuvant to boost vaccine efficacy. Continuous antigen exposure and immune stimulation provided by the implanted MNs may enhance the immunogenicity of influenza vaccines and evoke long-lasting immune responses to completely protect mice from lethal influenza challenge. The proposed MN system has great potential to be used as a new adjuvanted vaccine formulation and make influenza vaccination more effective and more accessible.